Sulfide Surface Dynamics on Cu(100) and Ag(100) Electrodes in the Presence of c(2×2) Halide Adlayers. Issue 20 (27th July 2018) - Rahn, Björn; Magnussen, Olaf M.
Abstract: The influence of coadsorbed anions on electrode surface dynamics is studied in situ by direct observation of single adsorbed species via high‐speed scanning tunneling microscopy. Using well‐defined model systems, sulfide adsorbates on Cu(100) and Ag(100) covered by c(2×2) ordered adlayers of chloride or bromide, the influence of halide coadsorbate and the metal substrate on the dynamic behavior is systematically evaluated and quantitatively analyzed. The sulfide tracer diffusion coefficients exhibit a pronounced exponential potential dependence in all systems, caused by the effect of the double layer's electric field on the diffusion barrier. The sulfide mobility in general decreases with potential, with the surprising exemption of the Br‐covered Cu(100) surface where it increases, indicating a different transport mechanism. In contrast to this strong influence of the halide species on the surface diffusion, the sulfide‐sulfide interactions seem to be less affected by the nature of the coadsorbate, but depend more strongly on the type of metal substrate. In addition, the dynamic behavior of clusters on the surface, the formation of grooves, caused by adsorbate‐induced vacancy generation, and the adlayer structure and dynamics at high sulfide coverage is discussed for bromide‐covered surfaces. The data indicate a tendency of bromide to enhance the transfer of sulfide adsorbates to sites within the metal surface layer. Abstract : Video evidence : the influence of coadsorbed halide (Cl, Br) ions on sulfide adsorbate dynamics on Cu(100) and Ag(100) electrodes is discussed. High speed scanning tunneling microscopy allows direct observation on the 100 ms timescale of single adsorbates on the electrode surface. These provide insight on the surface diffusion, adsorbate‐adsorbate interaction and interactions with the metal substrate for sulfide on these metals.